Estudo do biomarcador p16 no carcinoma de mama de mulheres submetidas à endocrinoterapia primária de curta duração com tamoxifeno e anastrozol - Melitto, Alexandre Santos [UNIFESP] (2009)
Background: Frequent deletions or mutations of the INK4 gene, which encodes the cyclin-dependent kinase 4 inhibitor p16INK4a, have been documented in various human cancers, but little is known about the role of this tumor suppressor gene in primary breast cancer and there is a lack in the literature about its expression behavior in neoadjuvant endocrinetherapy with tamoxifen or anastrozole. Objective: Analysis of p16INK4a expression in patients with invasive ductal carcinomas (IDC) prior to tamoxifen and anastrozole neoadjuvant treatment and possible correlation between predictive and prognostical factors – estrogen receptor (ER), progesterone receptor (PgR). Methods: We examined p16INK4a mRNA expression and its relationship with short period (26 days) neoadjuvant endocrine therapy with tamoxifen and anastrozole in 58 primary breast cancers with palpable ER-positive IDC. They were double-blind randomized in three neoadjuvant treatment groups for 21 days: Anastrozole 1mg/day (n= 17), Placebo (n=25) and Tamoxifen 20mg/day (n=15). Biomarkers status (ER, PgR and p16) were obtained by comparing single immunohistochemical evaluation of pre and post-surgery samples using Allred’s method. Statistical analyses were performed using the SPSS software for Windows. Results: Variation in p16 was 22% to 17% in anastrozole group, 8% to 4% in placebo group and there was no variation in tamoxifen group, standing in 7%. There was no significant statistical diference in p16INK4a expression among the three groups (p=0.17). Variation in p16 was 12% to 9% (p<0.05) when considering the three groups together. There was a significant decrease of p16 expression in pre and post surgery results. There was no significant statistical correlation between p16 expression and hormonal status (RE and RP). Conclusions: There was no significant statistical diference in p16INK4a expression among the three groups. There was a significant statistical decrease in p16INK4a expression when compared pre and post surgery values. These findings could indicate that expression of p16 and variation in pre and post surgery samples are associated with hormone responsiveness and mechanisms of resistance. There were no significant statistical correlation between p16 expression and hormonal status (RE and RP). Further studies are necessary to understand their functional interrelationships and whether high p16INK4a expression may be associated with a lack of hormone responsiveness in breast cancer.